2013
DOI: 10.1111/bjh.12593
|View full text |Cite
|
Sign up to set email alerts
|

Routine coagulation assays underestimate levels of antithrombin‐dependent drugs but not of direct anticoagulant drugs in plasma from patients with cirrhosis

Abstract: Summary There is increasing recognition that thrombotic complications may occur in patients with cirrhosis, and literature on antithrombotic treatment in these patients is rapidly emerging. Due to extensive haemostatic changes in patients with cirrhosis, careful monitoring of anticoagulant therapy may be required. Recent data suggest that plasma levels of low molecular weight heparin (LMWH) are substantially underestimated by the anti‐activated factor X (anti‐Xa) assay in patients with cirrhosis. We studied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 18 publications
0
99
1
1
Order By: Relevance
“…varices), but also to a loss of buffer capacity, in the sense that small variations of a pro- and anticoagulant protein will result more easily in an unbalanced situation. Therefore, we can expect that patients react differently to anticoagulation treatment than healthy controls, as shown in recent literature [44]. The most obvious case is the decreased effectiveness of treatment with heparins, because heparin acts by increasing the AT activity [4547].…”
Section: Discussionmentioning
confidence: 99%
“…varices), but also to a loss of buffer capacity, in the sense that small variations of a pro- and anticoagulant protein will result more easily in an unbalanced situation. Therefore, we can expect that patients react differently to anticoagulation treatment than healthy controls, as shown in recent literature [44]. The most obvious case is the decreased effectiveness of treatment with heparins, because heparin acts by increasing the AT activity [4547].…”
Section: Discussionmentioning
confidence: 99%
“…In following of these general limitations, our group has investigated whether chronic liver disease-related hemostatic changes affect the reliability of the assay to guide LMWH dosage [122]. We found that the anti-FXa assay systematically underestimated the LMWH dose administered in vitro to plasma of cirrhotic patients (without impaired renal function).…”
Section: Monitoring Of Antithrombotic Therapymentioning
confidence: 99%
“…These results suggest that anticoagulant treatment with these direct factor Xa inhibitors will likely not result in overanticoagulation, with a potentially increased bleeding risk, provided drug levels remain in the target range. Careful monitoring of drug levels, for example, by anti-Xa testing, 6 1 and subsequent response by the authors is reflective of the growing interest in the use of nontraditional anticoagulants for treatment of portal and superior mesenteric vein thrombosis (PVT/SMV) in patients with cirrhosis. Both factor Xa inhibitors exhibit reliable pharmacokinetics and pharmacodynamics, with a linear relation between plasma concentration of the drug and anticoagulant activity.…”
Section: Decreased In Vitro Anticoagulant Potency Of Rivaroxaban and mentioning
confidence: 99%